149k views
5 votes
2/3 (n - 6) = 5n - 43

PLEASE HELP! YOU WILL GET AT 12 POINTS SO PPLLLZZZ HELP

User JaTo
by
6.4k points

2 Answers

7 votes
Solve for n by simplifying both sides of the equation, then isolating the variable
n=9
User Hackattack
by
5.3k points
2 votes
There are several methods you could use, to solve this problem. I'll show you ONE way :)
Working:
- We need to expand the brackets first.
Thus,
multiply 2/3 to each term in side the bracket.
2 × n = 2n then divide 2n to the denominator.
2n ÷ 3 becomes, 2/3n.
Following same method:
2 × -6 = -12
-12 ÷ 3 = -4
Answer for the expanded form is; 2/3n - 4 = 5n - 43.
From here, you need to place the like terms on one side of the equation.
So,
2/3n - 5n = -43 + 4
-13/3n = -39
Then divide the coefficent (-13/3) on both sides.
n = 9

I'll upload a picture of my workings. It cuts of the question, but that's fine, you can still see the working out. Chur
Hope this makes sense :)



2/3 (n - 6) = 5n - 43 PLEASE HELP! YOU WILL GET AT 12 POINTS SO PPLLLZZZ HELP-example-1